One step cyclocondensation of (thio)barbituric acid with chalcones in glacial acetic acid and phosphorous pentoxide: Part-I - Akhter, K; Ahmed, SM; Halim, Md E; Kader, MA; Jahan, K; Romman, UKR; Ahmed, MG (Bangladesh Journal of Scientific and Industrial Research, 2016)
Some new 5, 7-diaryl-1,5-dihydro (or 1, 2, 3, 5-tetrahydro)- pyrano[2, 3-d] pyrimidin-2, 4-diones (or 2-thioxo-4-ones) (3a-h) have been synthesized in one-step by cyclocondensation of barbituric acid or thiobarbituric acid (1) with arylideneacetophenones (2a-d), in glacial acetic acid in the presence of phosphorous pentoxide. The structures of the compounds 3a-h have been determined by UV, IR, 1H NMR, 13C NMR, mass spectral data and elemental analyses. The compounds 3a-h do not seem to be available in the literature Bangladesh J. Sci. Ind. Res. 51(2), 129-138, 2016